Estimating the number of children in households with substance use disorders in Germany - Ludwig Kraus (BMC, 2021)
Abstract Background Parental substance misuse is reported to endanger the health and psychological development of children and adolescents. The aim of the present study was to address conceptual and methodological problems in estimating the number of children affected by parental substance misuse (CaPSM) and offer a novel approach based on survey data. Methods Data came from the 2018 German Epidemiological Survey of Substance Abuse (ESA) among 18- to 64-year-olds (n = 9267) and from population statistics. DSM-IV diagnostic criteria were used to assess substance use disorder (SUD) related to tobacco, alcohol, cannabis, cocaine or amphetamine. Based on the number of household members, the number of children below age 18 years and the information on SUD status of the respondent living in this household, the number of children currently living in households with at least one member with SUD was estimated. Results In 2018, there were 13,597,428 children younger than 18 years living in Germany. Of these, 6.9–12.3% (935,522–1,673,103) were estimated to currently live in households where at least one adult had a tobacco use disorder, 5.1–9.2% (688,111–1,257,345) in households where at least one adult had an alcohol use disorder and 0.6–1.2% (87,817–158,401) in households where at least one adult had a disorder related to the use of illicit drugs. The total number of children currently living with SUD adults in their household was estimated at 11.2–20.2% (1,521,495–2,751,796). Conclusions Available estimates are difficult to interpret and to compare due to a lack of clear case definitions and methodological approaches with various biases and limitations. Future estimates need to provide precise case definitions and standard approaches.